2017
DOI: 10.1016/j.envres.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to organophosphorus pesticides and childhood neurodevelopmental phenotypes

Abstract: Prenatal exposure to organophosphorus pesticides (OPs) has been associated with different neurodevelopmental outcomes across different cohorts. A phenotypic approach may address some of these differences by incorporating information across scales and accounting for the complex correlational structure of neurodevelopmental outcomes. Additionally, Bayesian hierarchical modeling can account for confounding by collinear co-exposures. We use this framework to examine associations between prenatal exposure to OPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 65 publications
(97 reference statements)
0
29
1
1
Order By: Relevance
“…Additionally, Zhang et al [ 79 ] and Mora et al [ 80 ] used Carbofuranphenol and Mancozeb compounds to assess CM exposure, whereas Keil et al [ 81 ] assessed Imidacloprid exposure, a NN pesticide. Finally, 9 out of 45 (20.0%) studies [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] reported exposure to a common mix of different types of pesticides. From all these studies, 37 out of 45 (82.2%) followed a longitudinal design, while only 8 (17.8%) were case-control studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Zhang et al [ 79 ] and Mora et al [ 80 ] used Carbofuranphenol and Mancozeb compounds to assess CM exposure, whereas Keil et al [ 81 ] assessed Imidacloprid exposure, a NN pesticide. Finally, 9 out of 45 (20.0%) studies [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] reported exposure to a common mix of different types of pesticides. From all these studies, 37 out of 45 (82.2%) followed a longitudinal design, while only 8 (17.8%) were case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the quality of the preclinical studies, three out of the 16 were labeled as H (18.8%) [ 30 , 37 , 38 ], 10 as MH (62.5%) [ 31 , 32 , 33 , 34 , 35 , 36 , 40 , 43 , 44 , 45 ], and the remaining three as ML-quality (18.8%) [ 39 , 41 , 42 ]. In a similar vein, 37 out of 45 human studies were classified as VH (82.2%) [ 46 , 48 , 49 , 50 , 51 , 52 , 53 , 56 , 57 , 58 , 59 , 61 , 63 , 64 , 65 , 66 , 67 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 80 , 81 , 82 , 83 , 84 , 85 , 87 , 88 , 89 , 90 , 91 ], 7 as H (15.6%) [ 47 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower IQ scores and impaired working memory were reported in different longitudinal studies at 7 years [3, 12, 42]. In contrast, a more recent study found a positive association between maternal DMP during pregnancy and maternal-reported measures of executive function in children aged 6–9 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus pesticides (OPs) are widely studied chemicals that can be absorbed by humans (3). Researchers have confirmed that prenatal exposure to OPs leads to neurodevelopmental disabilities and impairments (4)(5)(6). Chlorpyrifos (CPF) is one of the most widely used OPs in the world (7).…”
Section: Introductionmentioning
confidence: 99%